Copper (II) Oxide Nanoparticle As Friction Reduction and Anti-Wear Additive In Lubricating Oil - H. M., Asnida; Sakinah, Muhamad Hisham; M. M., Noor; K., Kadirgama; D., Ramasamy (2016)
Most lubricant available on the market are mineral based and synthetic. Several researcher tried to imptove the tribological behaviour of lubricating oil and one of the method is adding a suitable additive in the lubricant. The present work investigated the tribological behaviour properties of CuO nanoparticles in SYNTIUM 800 SL 10W-30 and nanoparticle added were dispersed using a sonicator water bath and oleic acid as surfactant for improved dispensability and stability of nanolubricant. All the test were performed under different parameter (load, concentration, and speed) moreover, RSM method has been used for design of experiment. The evaluated of the friction and wear properties between the moving testers were analysis the surface and composition at the specimen using the SEM and XDR. TEM also been used to investigate the agglomeration and stability of the lubricant consist additive. The result show that the CuO nanoparticles can effectively improve the engine oil lubricating properties and at the same time improve the tribological behaviour were reduce coefficient of friction and wear under certain condition. It found that, addition of CuO nanoparticles are most effective nanoparticles in the lubricant were appear the protection film for reduction the tribological behaviour at some limitation and other characteristics of the CuO additive.